Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/jjco/hyu074
|View full text |Cite
|
Sign up to set email alerts
|

Successful Crizotinib Rechallenge After Crizotinib-induced Interstitial Lung Disease

Abstract: We report the case of a 70-year-old Japanese male diagnosed with advanced lung adenocarcinoma harboring the echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase fusion gene. As soon as crizotinib was administered, tumor shrank immediately. On Day 25, he developed interstitial lung disease. Bronchoalveolar lavage fluid analysis demonstrated elevated lymphocytes fractionation. A drug lymphocyte stimulating test for crizotinib with the bronchoalveolar lavage lymphocytes was negative. Crizot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…After a systematic review of the literature, we identified 43 other cases of crizotinib-associated ILD, among which 34 were notified in the PROFILE studies and nine case reports described in more detail [10][11][12][13][14][15][16][17][18] (Table 3).…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After a systematic review of the literature, we identified 43 other cases of crizotinib-associated ILD, among which 34 were notified in the PROFILE studies and nine case reports described in more detail [10][11][12][13][14][15][16][17][18] (Table 3).…”
Section: Results Of Systematic Reviewmentioning
confidence: 99%
“…Other reported cases had few symptoms like ours (Table 3). 14,16,17 Crizotinib was restarted with corticosteroids, 12,16,17 except in one case. 14 This latter being the only which presented a relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some case reports have indicated successful crizotinib retreatment after crizotinib-induced ILD in patients with the non-DAD pattern, which was characterized by localized or faint ground-glass opacities. 17,30,31 Nevertheless, crizotinib retreatment should be performed under careful consideration of potential risks and benefits even in patients with ILD with the non-DAD pattern, and a careful monitoring is essential. Additionally, the ILD independent review committee reported 8 patients with pulmonary edema-like shadows among 117 patients with ILD, and these 8 patients had no other disease except for ILD, which can cause pulmonary edema-like shadows.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no defi nitive diagnosis was established for severe respiratory failure that made further examination difficult and required a prompt response. Crizotinib-induced pneumonitis was considered to be one of possible etiologies of respiratory insufficiency based on the previous reports, some of which showed successful retreatment with an ALK inhibitor after the development of pneumonitis [10][11][12][13] . Particularly, Chino et al reported an ALK-positive patient who had undergone crizotinib-induced pneumonitis was successfully treated with alectinib thereafter 13) .…”
Section: Discussionmentioning
confidence: 99%